New Glocal Forms of Financial Participation (Glocalism: Journal of Culture, Politics and Innovation, 2021)
Invited to peek into the mysterious and arcane academic glocal universe, I became intrigued by the range and depth of disciplines, theoretical perspectives and topics which the subject can embrace. Nonetheless, my impression is that, as ever in the economic world, power relations rest at the centre of globalisation-localisation and attendant debates. And so, it is with participation, which can be analysed at different levels and through different prisms, but my interests in these debates rest on the specific but essential question of organisational participation. Its elemental nature has taken on greater significance as the world faces existentialist crises as a consequence of unrestrained commercial activity made through decisions which directly affect working people and their communities, but over which they exercise little control.
Keywords: financial participation; glocalisation; worker cooperatives; employee-owned enterprises; remunicipalisation